The importance of selection bias in prospective birth cohort studies - Henrik Larsson (Wiley, 2021)
Abstract Sophisticated statistical analyses of data from large‐scale prospective birth cohort studies combined with thoughtful study designs have advanced understanding about the causes, consequences and developmental course of child and adolescent mental health problems. Available large‐scale prospective cohort studies, such as ALSPAC, MoBA, and TEDS have many noteworthy strengths, but they all suffer from non‐random non‐participation and attrition over time. Recent findings have highlighted that prospective birth cohort studies need to carefully consider the importance of selection bias.